Autocrine/Paracrine Slit–Robo Signaling Controls Optic Lobe Development in Drosophila melanogaster - González-Ramírez, M. Constanza; Rojo-Cortés, Francisca; Candia, Noemí; Garay-Montecinos, Jorge; Guzmán-Palma, Pablo; Campusano, Jorge M.; Oliva, Carlos (Frontiers in Cell and Developmental Biology, 2022)
Cell segregation mechanisms play essential roles during the development of the central nervous system (CNS) to support its organization into distinct compartments. The Slit protein is a secreted signal, classically considered a paracrine repellent for axonal growth through Robo receptors. However, its function in the compartmentalization of CNS is less explored. In this work, we show that Slit and Robo3 are expressed in the same neuronal population of the Drosophila optic lobe, where they are required for the correct compartmentalization of optic lobe neuropils by the action of an autocrine/paracrine mechanism. We characterized the endocytic route followed by the Slit/Robo3 complex and detected genetic interactions with genes involved in endocytosis and actin dynamics. Thus, we report that the Slit-Robo3 pathway regulates the morphogenesis of the optic lobe through an atypical autocrine/paracrine mechanism in addition to its role in axon guidance, and in association with proteins of the endocytic pathway and small GTPases.